Prevalence, antibiotic resistance, PFGE and MLST characterization of Salmonella in swine mesenteric lymph nodes - Possebon, Fábio Sossai [UNESP]; Tiba Casas, Monique Ribeiro; Nero, Luís Augusto; Yamatogi, Ricardo Seiti; Araújo Jr., João Pessoa [UNESP]; Pinto, José Paes de Almeida Nogueira [UNESP] (Elsevier, 2020)
This study evaluated 250 animals from 25 different processing lots, processed in four slaughterhouses in São Paulo state, Brazil for the presence of Salmonella in the mesenteric lymph nodes (10 g sample of each animal) and characterized the antibiotics resistance profile, the Pulsed Field Gel Electrophoresis – PFGE and Multi Locus Sequence Typing – MLST profiles of selected strains. The pathogen was present in 36.4% (n = 91, CL 95% 30.4–43.4) of samples and 72% (n = 18, CL 95% 50.6–87.9%) of the analyzed lots. The main serovars were S. Typhimurium (n = 23), Salmonella enterica subsp. enterica 1.4,5,12:i:- (n = 17), followed by S. Infantis (n = 12) and S. Havana (n = 11). Twenty-eight strains (30%) were classified as other serovars. Sixty-eight percent of the strains were resistant to Streptomycin and tetracycline, followed by ampicillin and sulphonamides (62.6%), chloramphenicol (56.0%), trimethoprim-sulfamethoxazole (41.8%) and nalidixic acid (40.7%). The antibiotics with lower resistance rates were cephalothin and aztreonam (both with 3.3% resistant), and ceftriaxone and cefepime (both with 7.7%). Multidrug-resistant strains (MDR) accounted for 70.3% of the isolates. Eight strains were submitted to MLST: four S. Typhimurium and one S.1.4,5,12:i:-, all belonging to the ST 19, two Salmonella Infantis, belonging to the ST 32 and one S. Derby, belonging to ST 40. Twenty-one isolates with different antibiotics resistance profiles from the most prevalent serovars were selected for PFGE analysis. Serovar S. Typhimurium (n = 11) revealed 4 pulsotypes and 1 cluster and S. 1.4,5,12:i:- (n = 10) revealed 5 pulsotypes and 4 clusters. The high prevalence of the pathogen, with its high rates of antibiotics resistance and belonging to genetic groups that are often associated with disease in humans, shows that the production chain of pork is a potential source of infection in salmonellosis cases. Therefore, effective preventive measures for pathogen control are needed to reduce the risk of foodborne diseases.
Keywords: Molecular epidemiology; Monophasic Salmonella; Pork